The private, the Virus and the Leviathan: The Sars-Cov-2 Crisis and the Metamorphosis of the State - Joaquín Rodríguez Álvarez (Journal of Law, 2020)
Along the last decades, especially after the Regan-Thatcher de-regulation period, we have assisted to the dismantling of the State, from its conceptualization as a manager of the Common-Good and the embodied of the Common-interest (Rousseau), to its transformation into a formula of indirect private government produced by the constant privatization of basic services such as security, healthcare or education, and the transfer of wealth from the middle and low class to the upper elite. A pattern that represents the destruction of the fundamental pillars that have gestated the very first formula of the liberal state. A transformation, that has been practical, as well as psychological, deeply affecting the behavior we develop as member of a society where values such as solidarity has been completely overcome by a social Darwinism. Having as main consequences the constant degradation of the democratic process and the erosion of the system of check and balances. Through this article, we aim to analyze how the response to the Sars-CoV- 2 represents the dissolution of the State, showing the configuration of a system, that tends to “privatize” the government interest. While affirming a very complex phenomenon that we could describe as the “return to authoritarian formulas”.